The Relationship between Problem-Solving Skills and Student Academic Achievement: A Meta-Analysis in Education - Banawi , Anasufi; Rumasoreng, Muhammad Irfan; Hasanah , Nur; Rahawarin, Darwis Amin; Basta, Irawati (Journal of Ecohumanism, 2024)
The use of meta-analysis allows the results obtained to be representative, and meta-analysis of the correlation between problem-solving skills and students' learning outcomes and/or achievements is no exception. Problem-solving skills are very important for students in various learning contexts. This study aims to describe the relationship and effects of problem-solving skills on learning outcomes and or student achievement. This study used a descriptive quantitative method using meta-analysis that focuses on the relationship between two or more variables. The meta-analysis was conducted on 22 articles selected from the screening of articles from 2008-2023 in the SINTA (Science and Technology Index) and Garuda (Garba Rujukan Digital) databases. The results showed that the impact of problem-solving ability on learning outcomes and achievement was very significant at 84.8%. There is a strong positive correlation (r = 0.69) between problem-solving ability and student learning outcomes and/or achievement. The distribution of studies in this meta-analysis is relatively symmetrical, and there is no publication bias. Nonetheless, it is necessary to consider potential sources of heterogeneity when applying these findings to educational practice.